2022
DOI: 10.1016/j.envint.2021.106887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 containment and closure policies on tropospheric nitrogen dioxide: A global perspective

Abstract: The containment and closure policies adopted in attempts to contain the spread of the 2019 coronavirus disease (COVID-19) have impacted nearly every aspect of our lives including the environment we live in. These influences may be observed when evaluating changes in pollutants such as nitrogen dioxide (NO 2 ), which is an important indicator for economic, industrial, and other anthropogenic activities. We utilized a data-driven approach to analyze the relationship between tropospheric NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Beyond the effects of policies on NO2 anomalies widely discussed in many studies [7][8]18], the main novelty and contributions lied in that this study succeed to tell the difference of human activity containment and quantify their contributions to NO2 anomalies. The top three measures showing dominant effects were C2 "Workplace closure", C5 "Restricted public transport usage", and C1 "School closure", accounting for 54.8%, 52.3%, and 46.4%, respectively.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Beyond the effects of policies on NO2 anomalies widely discussed in many studies [7][8]18], the main novelty and contributions lied in that this study succeed to tell the difference of human activity containment and quantify their contributions to NO2 anomalies. The top three measures showing dominant effects were C2 "Workplace closure", C5 "Restricted public transport usage", and C1 "School closure", accounting for 54.8%, 52.3%, and 46.4%, respectively.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…More specifically, NO2 concentrations derived from TROPOMI in Beijing decreased by 45% in March 2020 [9], while ground-based NO2 concentrations in Beijing decreased by 41.8% compared with the previous 3-year average level, and by 33.7% compared to 2019 [22]; one recent study from global perspective, showed that the COVID-19 outbreak explained reductions in NO2, from OMI and TROPOMI, by only 6% averagely in China when considering meteorology effects [7]. Another globally study based on OMI showed that NO2 level between January and February was seen a drastic reduction while it further observed to rise in the March and April 2020 [18]. As spatial heterogeneity of NO2 anomalies have been confirmed, the differences between observations recall that research findings may vary due to different spatial scales regarding the Modifiable Areal Unit Problem (MAUP) [23].…”
Section: Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…Li et al 38 showed that the COVID-19 containment and closure policies did not significantly reduce NO 2 tropospheric NO 2 vertical column density (TVCD) in the mild or moderate clusters, but they did so in the poor cluster. They utilized the SI for monitoring pandemic restrictions like in our study and demonstrated that specifically, a rise of 1 SD (23.58) in the SI is associated with a drop of 3.2% NO 2 TVCD in the poor cluster (coefficient = −0.033, P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of CO 2 emissions in Italy shows a stable downward trend: in 2010, the volume of emissions was 397.1 million tons of CO 2 , in 2020-317.1 million tons of CO 2 , i.e., a decrease of 20.1%. It should be noted that in 2020, the global emissions indicator decreased due to the restrictions imposed due to the COVID-19 pandemic [48].…”
Section: Italian and Russian Energy Sectors: Key Trends And Differencesmentioning
confidence: 99%